Material de enseñanza de los grupos funcionales de la química orgánica, desde el uso de la especie vegetal limoncillo (Cymbopogon Citratus) en la medicina indígena ancestral de la comunidad Yaporogos Taira. (2021)
This work was designed as a didactic strategy for the teaching of the functional groups of organic chemistry, from the extraction of the essential oil of the plant species Lemongrass (Cymbopogon citratus), used in the ancestral indigenous medicine of the Yaporogos Taira community. which is located in the urban and rural area of ​​the municipality from Prado-Tolima (specifically in the urban area and in the paths of Tomogó, Isla del Sol and Conchal).